A comparative study of charge trapping effect in p-type MoTe2 and WSe2 FETs using pulsed current–voltage measurements. (8th January 2021) - Yang, Jeong Yong; Lee, Chan Ho; Oh, Young Taek; Ma, Jiyeon; Heo, Junseok; Yoo, Geonwook
Abstract: P-type semiconductors are indispensable for achieving complementary metal oxide semiconductor and integrated circuits based on two-dimensional (2D) semiconductors, and tungsten diselenide (WSe2 ) and molybdenum ditelluride (MoTe2 ) are the promising channel materials for PMOS. In this work, we report on the charge trapping effects on hysteretic behavior and field-effect mobility ( μ FE ) of the p-type WSe2 and MoTe2 FETs using fast pulsed current–voltage ( I – V ) measurements. The hysteresis is reduced by nearly 98% via ramped pulsed measurements, and μ FE is significantly enhanced via single pulse measurements by minimizing the charge trapping. Moreover, WSe2 FETs are found to be more susceptible to the charge trapping effects compared with MoTe2 FETs; WSe2 FETs exhibit more pronounced enhancement of μ FE and reduction of hysteresis. The intrinsic electrical characteristics of p-type 2D FETs under minimized charge trapping conditions can be investigated using the pulsed I – V characterizations.